2001
DOI: 10.1159/000046117
|View full text |Cite
|
Sign up to set email alerts
|

Crescent-Forming Mechanism in an Irreversible Thy-1 Model in Rats

Abstract: Background: The crescent-forming mechanism has not yet been fully clarified and a cell which constitutes a crescent still remains controversial. This study was undertaken to analyze the crescent-forming mechanism in an irreversible Thy-1 model by applying a new marker-recognizing monoclonal antibody (mAb) OS-3. Methods: An irreversible Thy-1 model was induced by an intravenous injection of 500 µg of anti-Thy-1 mAb 1-22-3 to unilaterally nephrectomized Wistar rats. Seven rats were sacrificed 3, 7 and 14 days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…CCN1-negative podocytes may contribute to the pathological lesion seen in IgAN in two ways: first, a decrease in GBM-bound CCN1 may enhance mesangial migration, which leads to glomerular tuft occlusion and to glomerulosclerosis. Second, excessive podocyte migration can lead to podocyte bridging, and further on to glomerular crescent formation (17,20,23,26,30,31). The functional significance of CCN1 downregulation in IgAN should await further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…CCN1-negative podocytes may contribute to the pathological lesion seen in IgAN in two ways: first, a decrease in GBM-bound CCN1 may enhance mesangial migration, which leads to glomerular tuft occlusion and to glomerulosclerosis. Second, excessive podocyte migration can lead to podocyte bridging, and further on to glomerular crescent formation (17,20,23,26,30,31). The functional significance of CCN1 downregulation in IgAN should await further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies of anti-Thy1 models of glomerulonephritis have previously been performed (1,3,4,10,11,16,17,18); the overall course of the disease, the mechanisms of disease biogenesis, and even many details of repair regulation are known. However, the multiform lesions encountered in glomeruli and tubules have never been integrated into a unified concept of damage development.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Although Thy-1 nephritis is basically MsPGN, crescents were observed in some studies of Thy-1 nephritis as reported by us and another study group. 13,36,37 In our previous study, treatment with prednisolone for rat Thy-1 nephritis inhibited both crescent formation and mesangial cell proliferation, although prednisolone does not suppress fibrin precipitation in Bowman's space; 36 therefore, the use of a specific factor Xa inhibitor may take advantage of antithrombotic and antiproliferative effects in crescent formation in MsPGN.…”
Section: Roles Of Factor Xa In Rat Mspgnmentioning
confidence: 92%
“…It has been reported that acute injury of the glomerulus in Thy-1 nephritis is mainly initiated by necrosis 12 and apoptosis of mesangial cells, and is often accompanied by cellular crescent formation. 13 Subsequent mesangial cell proliferation is an important pathophysiological phenomenon found in various glomerular diseases, often resulting in end-stage renal disease. 14 The aim of the present study, therefore, was to clarify the roles of the coagulation process in proliferative responses in MsPGN.…”
mentioning
confidence: 99%